2021
DOI: 10.1088/1755-1315/810/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Gluten-Free Starch and the Application on Cookies

Abstract: Flour is a raw material widely used in the manufacture of food products, but the gluten content in flour can cause allergies, especially in people with Celiac Diseases. Therefor, it is needed to find alternative raw materials for flour. One way to replace flour is to use gluten-free starch and modify it to obtain specific characteristics. In this study, modifications were made to several starches, namely canna starch, cassava starch, and taro starch, by a cross-linking method using Sodium Tripolyphosphate (STP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Taro starch had a starch content of 67.7%, 23.8% amylose content, 14.8% swelling power, and 21.9% solubility. The sensory evaluation revealed that the majority of panelists enjoy cookies produced with modified taro starch (Yesi & Sugiarti, 2021 ).…”
Section: Application Of Taro Starch In Food Industrymentioning
confidence: 99%
“…Taro starch had a starch content of 67.7%, 23.8% amylose content, 14.8% swelling power, and 21.9% solubility. The sensory evaluation revealed that the majority of panelists enjoy cookies produced with modified taro starch (Yesi & Sugiarti, 2021 ).…”
Section: Application Of Taro Starch In Food Industrymentioning
confidence: 99%